DOZIRANJE OPTEREĆENJA U REKREACIJI - MODEL VJEŽBANJA: Trčanje u mjestu 10 x 1 min sa 10 x 1 min odmora - Budimir Bijelić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Individual needs, motifs, desires, interests and similar reasons determine everyday the individuals of all social - aged categories to active involvement in to various programmes and activities in the field of sports recreation. A concept of "individual sports recreation" means for the activity in which one can determine independently: the time of doing exercise; a manner of conducting the activities (on one's own, with trainers, with member(s) of a family and like wise); a place of conducting the activities (an appartment, a house or similar places for living or relaxing) and furthermore in which one can perform the programmes of exercise adapted to one's own capabilities and other personal requirements.The Paper deals with characteristics of some efficient (for general aerobic capabilities) individual patterns of doing exercise for all social - aged and the intensively capable categories of participants. The pattern of doing exercise covered 10 x 1 min. of running in place and 10 x 1 min. of quick recoveries between the series, and then five - minutes of individual exercise after a complete set of exercise. Checking out of the characteristics of this pattern of individually done exercise (sampling with students) in this research has confirmed its wide practical applicability for gaining, maintaining and testing aerobic capabilities of the individuals (especially beginners in recreation).